Two Cases of Preoperatively Diagnosed Ileosigmoid Knot - Taga, Satoshi; Etoh, Eiichi; Yano, Koichi; Shimauchi, Takahiro; Akimoto, Hisafumi; Ueno, Yosuke; Ishida, Shingo; Kamachi, Kenichi; Niijima, Natsuko (Nippon Shokaki Geka Gakkai zasshi, 2012)
Intestinal knots can rarely cause acute abdomen. Knots in the ileum and sigmoid colon are called ileosigmoid knots (ISK). We encountered 2 cases of ISK, which we were able to diagnose preoperatively. In case 1, a loop of ileum was wrapped around the base of the sigmoid colon in a clockwise direction, leading to the formation of a knot; we diagnosed this as ISK type IA. Partial resection of the ileum was performed. The clinical course was good without any complications. In case 2, a loop of the sigmoid colon was wrapped around the base of the ileum in a clockwise direction, causing intestinal obstruction; we diagnosed this as ISK type IIA. The sigmoid colon showed necrotic changes requiring resection. The patient died the day after surgery due to septic shock. ISK is a rare cause of ileus (about 1% of intestinal obstruction cases). The preoperative diagnosis of ISK is difficult, however, we were able to diagnose ISK before surgery by identifying important characteristics such as a "whirl sign" and double closed loop.